Isolation and Identification of Bioactive Compounds from Bacillus Megateriume5 from the South East Coastal Region of India against Urinary Tract Infectious Pathogens - Raj Kumar, K (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Identification of Bioactive Compounds from Bacillus Megateriume5 from the South East Coastal Region of India against Urinary Tract Infectious Pathogens